Narzędzia efektywnego zarządzania projektami logistycznymi - Wąsowicz, Marek (Tools of Effective Management of Logistic Projects, 2008)
The article presents the tools improving the effectiveness of conducted logistic projects Special attention is paid to present the software which pupports projects' management and knowledge management in a project. The solutions which are presented in the article let achieve the project's aims faster and with more effective usage of available resources.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 77-86